ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN JASA TRANSPORTASI PADA PT. CAKRA TRANSPORT UTAMA - Firmani, Putu Siti (Widyadari : Jurnal Pendidikan, 2018)
The development of the transportation service industry currently plays an important and rapidly growing role in the distribution (transport or delivery) of goods and services distributed to consumers in a country. Transportation services provided by the company have advantages offered to consumers. Marketing strategy becomes an important thing that must be done by the company to realize the maximum level of customer satisfaction but also to keep consumers from moving to other transportation service companies. PT Cakra Transport Utama is one of the tourism transportation services in the Bali area, in cooperation with one of Bali's many star hotels, many tourists from outside the region and tourists from abroad who come to spend time with family in Bali. This study aims to analyze the effects of tangible, reliability, responsiveness, assurance, and empathy on customer satisfaction. This study took sample of guest who use transportation services at Cakra Transport Utama, the number of samples used in this research is as many as 100 respondents. The result of analysis shows that physical evidence variable (X1) has regression coefficient 0,271 (positive sign) to consumer satisfaction (Y) and tcount 3,430 with significance level 0,001, reliability (X2) has regression coefficient 0,197 (positive sign) to satisfaction consumer (Y) and tcount of 2,318 with significance level 0,023, responsiveness (X3) has regression coefficient equal to 0,201 (marked positive) to consumer satisfaction (Y) and tcount 2,688 with significance level 0,008, assurance (X4) has coefficient regression of 0.316 (positive mark) on customer satisfaction (Y) and tcount of 3,959 with significance level 0,000, concern (X5) has a regression coefficient of 0.165 (positive mark) on consumer satisfaction (Y) and tcount of 2,095 with significance level 0.039. Adjusted R square value is 0.517. This means that 51.7% of consumer satisfaction (Y) can be explained by physical evidence variables (X1), reliability (X2), responsiveness (X3), assurance (X4), and concern (X5).